Storytelling in instant messenger communication. Sequencing a story without turn-taking. (October 2021) - Meiler, Matthias
Highlights: Telling stories is an activity routinely and jointly conducted in everyday life. It is important for participating in society and processing personal experiences. Instant messenger communication soaks through our everyday life. Almost nothing is known about how people type stories in instant messengers. This study is the first that explores the repertoire of how this can be done. Abstract: Everyday storytelling in private instant messenger communication is surprisingly understudied although it is to be considered a linguistic activity of high importance for the everyday life of the interlocutors in these days. This paper undertakes exploratory analyses of stories typed under the media conditions of instant messaging and outlines the spectrum of adaptation strategies that accompany the transposition from face-to-face to instant messengers. The analyses here focus especially on the interactional techniques of sequencing a story. This focus is due to specific media differences between face-to-face and instant messenger communication which have as one result that the latter lacks the temporal dynamics of turn-taking. The study's corpus comprises 40 instances of storytelling. The findings show a broad spectrum of possible techniques of telling a story under the specific media conditions of messenger communication: On the one end of the spectrum, one can find techniques clearly borrowed from face-to-face conversation and, on the other end, techniques that exploit the affordances of instant messaging paying special regard to its advantages.